Validation of a method employing liquid chromatography to identify and quantify glycomacropeptide of casein in raw milk - Bernal Chia, Orlando; Murcia Rubiano, Fernando; Ávila Guzmán, Olga Lucía; Guzman Gualteros, Jenifer Yaneth; Arias Casallas, Willinton Arturo; Morales, Maria Victoria (Vitae, 2021)
BACKGROUND: The information on official testing methods, or regulatory methods in Colombia to test whey in milk is limited; this restriction of information goes against the possibility of mitigating the risk of food fraud. OBJECTIVES: The validation of an HPLC method to determine casein glycomacropeptide (c-GMP), a protein that countries such as Brazil, Spain, and Ecuador have used as an indicator of raw milk adulteration with whey, was carried out. METHODS: A 10mL sample of raw milk is precipitated with 24% TCA using ultrasound, a process followed by filtration. The collected fraction ensured the separation of c-GMP and then injected into the liquid chromatography. RESULTS: A 30 minutes analysis allowed the determination of c-GMP with a retention time of 12.9 ± 0.5 minutes. The performance characteristics method in the validation exercise were: recovery percentage 99.97%, linearity R2> 0.95; % RSD accuracy <5.3%. CONCLUSION, the method exhibits desirable attributes for the intended purpose.